REVITALISASI KAWASAN PARIWISATA BERBASIS BUDAYA UNTUK MENINGKATKAN EKSISTENSI BUDAYA LOKAL DI KABUPATEN BULELENG - Widyani Nyoman (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Research on the revitalization of local culture-based tourism area aims to describe: (1) cultural values that can be used in tourism sector in Buleleng, (2) revitalization strategy of local culture-based tourism area that can be used to improve the existence of local culture in Buleleng. This research is a qualitative descriptive research. Informants in this research are cultural and community who work in the cultural and tourism sector. Data were collected by interview. Data analysis was done by descriptive method. The result of revitalization research of local culture-based tourism area shows that: local cultural values (Buleleng) that can be used in tourism sector are cultural values based on Tri Hita Karana philosophy. Implementation of the concept of parahyangan can be done by building places of worship around the tourist area, conducting praying activities. Implementation of the concept of pawongan can be done by greeting each other with